(untitled) (INTEGRATION PROCEEDING, 2023)
Stroke is one of the probable disease that causes paralysis of the limbs. Stroke patients require comprehensive treatment, including long-term recovery and rehabilitation efforts, even for the rest of the patient’s life. The family plays an important role in this recovery phase, so from the start of treatment the family is expected to be involved in patient care. Family knowledge in the care of post-stroke patients is very important to be able to accelerate the independence of post-stroke patients. This study aims to determine the relationship between family health behavior and increasing the functional capacity of post-stroke patients in the Dwikora Medan Area by 2022. The type of research is cross sectional. The study population was a family of post-stroke patients, totaling 30 people. The sampling technique used total sampling. Data collection in this study was carried out by distributing questionnaires directly to families. The statistical test used is the spearman rank. Based on the results of research conducted in the Dwikora area of ​​Medan that family knowledge in increasing the functional capacity of post-stroke patients was a sufficient majority of 15 people (56.7%), both 13 people (43.3%) and less than 2 people (6, 7%). The attitude of the family in increasing functional capacity after stroke was a good majority of 15 people (50.0%), quite a number of 11 people (36.7%) and less a number of 4 people (13.3%). Meanwhile, family action in increasing functional capacity after stroke was sufficient for the majority of 17 people (56.7%), good for 11 people (36.7%) and less for 2 people (6.7%). It is hoped that the family will carry out its role by increasing knowledge, attitudes and actions, so that the patient can be independent.